A regulação e a emancipação em escolas públicas localizadas no campo - Polon , Sandra Aparecida Machado (2012)
This thesis argues that regulatory processes are strategically adapted in schools, whereas emancipatory processes, in order to become effective, require studies and a collective willingness to question school practices, educational policies and, as a consequence the Political-Pedagogical Project. This study was carried out in 2012, 2013 and 2014 according to a qualitative approach and participatory research that included a bibliographical and documental study in addition to countryside research by means of 77 interviews and observations in 15 basic public schools – Basic School from 1st to 5th years - in Lapa, Paraná. The research analyzed the regulatory and emancipatory processes, Countryside Education and the Political-Pedagogical Project in order to answer the following question: Focusing on the PPP, how is regulation and emancipation produced in publics schools situated in the countryside? The study pointed out the elements that generate regulation as well as those that generate emancipatory processes. The context investigated demonstrated the regulatory marks related to the construction of the PPPs: deadlines for the elaboration or reformulation, which in many occasions hinder the study and a deeper theoretical understanding by teachers; guidelines as normative tools that inform what should or should not be part of the PPPs of the public schools situated in the countryside; the perpetuation of historical practices – economic, social and political in the school routine, which in turn dictate the perpetuation of schools didactic-pedagogical organization, according to current models, and that serve to political interests linked to the propagation of a capitalist ideology, that is, a clientelism relationship.